(untitled) (Research, Society and Development, 2024)
Objective: To map the scientific evidence on health technologies developed for the care of the elderly with stroke at home. Methodology: Scope review protocol according to the methodological recommendations of the Joanna Briggs Institute (JBI) and the Preferred Reporting Items for Systematic Review and Meta-Analyses Extension for Scoping Reviews (PRISMA-scr) The strategy of the information sources will be the databases and electronic libraries selected, in addition to the gray literatures. Three blinded independent reviewers will screen according to the pre-defined inclusion criteria. For data extraction will be used an instrument developed and tested by the reviewers. Regarding the analysis and presentation of the results will be analyzed to reflect the main themes and presented in a descriptive way, using figure, table or graph. Expected results: It will enable a broader visualization of the technologies used, as well as stimulate the creation and innovation of new technologies. Conclusion: This study will promote a comprehensive knowledge about the technologies developed, being essential to contribute to evidence-based practice.